Synthesis and Characterization of Thorium(IV) Complexes of 2,3-dimethyl-1-phenyl-4- (2-hydroxy-5-methyl phenyl azo)-pyrazol-5-one - Harikumaran Nair, M.L.; Mariamma, A.T. (Asian Journal of Chemistry, 2010)
Five new Th(IV) complexes of an azo dye, 2,3-dimethyl-1-phenyl-4-(2-hydroxy-5-methylphenylazo)- pyrazol-5-one (cresol azo antipyrine, CAAPH) have been prepared and characterized by elemental analysis, magnetic moment and conductance measurements, IR and NMR spectral studies. The thermal behaviour of one of the complexes has also been examined. On the basis of the above studies, the complexes confirm the composition [Th(CAAPH)2X4], where X = NO3–, NCS–, Cl–, I– or ClO4–. The X-ray powder diffraction patterns of the complex [Th(CAAPH)2Cl4] has been examined and found to be orthorhombic with the unit cell dimensions a = 15.4185 Å, b = 9.7577 Å and c = 7.2784 Å.